The correlation between multiple intelligence scores and English language reading skill among Business Management students / Nuramirah Zaini - Zaini, Nuramirah (Universiti Teknologi MARA, Perlis, 2019)
The growth of methods in doing business has made it vital for students in that area to be exposed to their Multiple Intelligence in relation with their skills in English Language. Concerning the fact that English is a universal language and reading is one of the fundamental skills in marketing, it is essential for the students to recognize their Multiple Intelligence to determine their best approach in doing business. Thus, a study was carried out among Business Management students in UiTM Alor Gajah Melaka to identify the relationship of Multiple Intelligence and the students' performance on two types of reading texts which are the linear and non-linear. The findings show that the most significant Intelligence of the students is interrelated with their reading skills. Indeed, it is necessary for the students in Business Studies to get exposed to their significant Intelligence especially its relation in the skills of using English as a medium of communication in written and spoken forms